Juliusz Słowacki in the Holy Land in 1837 - Jastrzębowska, Elżbieta (Palestine exploration quarterly, 2024)
The Polish poet Juliusz Słowacki (1809–1849) travelled through Palestine between 2 January and 27 January 1837, from El-Arish on the southern border with Egypt, at that time quarantined owing to plague, to the area around Lake Tiberias in the north, which had just been devastated by a strong earthquake. A detailed analysis of the itinerary of this pilgrimage has made it possible to establish new circumstances and topographical facts. The poet’s recently discovered personal diary (Raptularz Wschodni) contains hitherto unknown observations and drawings by the author himself. Together with his other travel notes and recollections in his letters, they constitute an invaluable basis for a new account of how and where he wandered, and where he stayed and spent the night. The published accounts of other 19th-century travellers in Palestine have helped establish further details: three Polish Roman Catholic priests, two French intellectuals, and the English aristocrat and globetrotter G. Robinson, as well as site views by D. Roberts. The traditional and often erroneous identification and dating of the sites visited by Słowacki have been verified on the basis of scientific historical and archaeological research as well as the author's own observations in situ in Israel and her interviews with Franciscan archivists. As far as the extensive modern Polish literature on this journey concerns, the novelty here lies in identifying features in three of Slowacki’s drawings and determining the places where the poet stayed in the Franciscan hospices in Ramla, Jerusalem, Bethlehem and Nazareth.